PRAKTIK PERNIKAHAN ISLAM AHAI VAU DI DESA FEER, KEI BESAR SELATAN, MALUKU TENGGARA - Rahayaan, Ahmad; Ikhwanuddin, Mohammad; Ibn Hamzah, Saiful (LP2M UIN Sayyid Ali Rahmatullah Tulungagung, 2022)
The intersection of religion and culture in Indonesia often provides new patterns in religious practice, including marriage. For example, the islamic marriage of Ahai Vau (cross-social class) in Feer, Kei Besar Selatan, Southeast Maluku. There are three social classs, namely mel-mel (top), riy-riy (middle), and ren-ren (bottom). This cultural prohibition consisted of the term kafā'ah in Islam. This study aimed to determine the practice of Ahai Vau marriage in Per Village and analyzed it from the concept of Kafā'ah (equality) in Islam. This type of research used descriptive-qualitative techniques, with the method of observation and interviews in data collection. The results showed that the practice of Ahai Vau Islamic marriage in Per still placed social class status as a necessity. So crosssocial class marriage was prohibited and considered a violation of customs. In Islam, someplace Kafā'ah is a condition for a valid marriage, but most scholars prefer to place Kafā'ah as a condition of luzum, a condition that must exist. Social class in Ahai Vau marriage is not a requirement for marriage because there are still two choices, cross-social class marriage, while carried out outside the village, and inter-tribal marriage.